Wonderfalls. The complete viewer collection - Holland, Todd.; Fuller, Bryan; Dhavernas, Caroline; Leitso, Tyron; Regency Television (Firm); LC Purchase Collection (Library of Congress) (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2005)
"Although a recent graduate of Brown University, Jaye Tyler decides to ignore her degree, live in a trailer and work at a tourist gift shop in Niagara Falls called Wonderfalls--much to the despair of her well-to-do family. But Jaye's aimless life takes a startling turn after a lion figurine begins talking to her. Her family calls it an "episode", but Jaye know better. Fearing for her sanity, Jaye nevertheless starts doing exactly what an increasing number of inanimate objects tell her to do and is amazed when her outrageous action begin changing people's live in unexpected ways"--Container.
disc 1. Wax lion ; Pink flamingos ; Karma penguin ; Wound-up penguin -- disc 2. Crime dog ; Muffin buffalo ; Barrel bear ; Lovesick ass -- disc 3. Safety canary ; Lying pig ; Cocktail bunny ; Totem mole ; Caged bird.
Dual layer.
Title from container.
Originally broadcast by Fox in 2004.
Special features: "Greetings from Wonderfalls" documentary; visual effects featurette; music video.
Caroline Dhavernas, Tyron Leitso.
Not rated.
Keywords: Gift shops -- New York -- Niagara Falls -- Drama; Gift shops -- Employees -- Drama; Television comedies; Fiction television programs; Video recordings for the hearing impaired